Meat crust as a novel food ingredient to regulate lipid peroxidation and oxidative stress - Eylon Asido; Haim Zeigerman; Michal Verman; Nurit Argov-Argaman; Joseph Kanner; Oren Tirosh (Current Research in Food Science, 2024)
Pan Fry (PF) is a common heating treatment however, there is limited data on meat oxidation after PF using direct contact with an uncoated iron pan. After PF, a crust is formed, and in this study, we aim to evaluate the potential anti-oxidation and anti-lipid peroxidation capacity of such crust. Ground beef and turkey meat were heat treated using PF or microwave. Lipid peroxidation was evaluated using malondialdehyde accumulation. PF meat generated lower lipid peroxidation levels versus microwave-heated meat. Iron PF has decreased lipid peroxidation versus Teflon pan heating. The crust significantly lowered lipid peroxidation and possessed millard reaction products (MRPs), strong reducing abilities, iodine removal capacity, and some iron chelation capacity. We demonstrated that the crust substantially decreases lipid peroxidation levels in various systems and can be used as a novel seminatural antioxidant ingredient, which may lead to extended shelf life and protects various food products.